The contribution of halos with different mass ratios to the overall growth of cluster-sized halos - Lemze, Doron; Zitrin, Adi; Bartelmann, Matthias (The astrophysical journal, 2013)
We provide a new observational test for a key prediction of the ΛCDM cosmological model: the contributions of mergers with different halo-to-main-cluster mass ratios to cluster-sized halo growth. We perform this test by dynamically analyzing 7 galaxy clusters, spanning the redshift range 0.13 < z c < 0.45 and caustic mass range 0.4-1.5 ##IMG## [http://ej.iop.org/images/0004-637X/776/2/91/apj483336ieqn1.gif] $10^15\, h_0.73^-1$ M ☉ , with an average of 293 spectroscopically confirmed bound galaxies to each cluster. The large radial coverage (a few virial radii), which covers the whole infall region, with a high number of spectroscopically identified galaxies enables this new study. For each cluster, we identify bound galaxies. Out of these galaxies, we identify infalling and accreted halos and estimate their masses and their dynamical states. Using the estimated masses, we derive the contribution of different mass ratios to cluster-sized halo growth. For mass ratios between 0.2 and 0.7, we find a 1σ agreement with ΛCDM expectations based on the Millennium simulations I and II. At low mass ratios, ##IMG## [http://ej.iop.org/icons/Entities/lsim.gif] lsim 0.2, our derived contribution is underestimated since the detection efficiency decreases at low masses, 2 × 10 14 ##IMG## [http://ej.iop.org/images/0004-637X/776/2/91/apj483336ieqn2.gif]